2011
DOI: 10.1002/eji.201041039
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐presentation capacity of dendritic cells is impaired in ongoing enterovirus myocarditis

Abstract: Coxsackievirus B3 (CVB3)‐infection is a frequent cause of acute myocarditis, which may result in chronic myocarditis and virus persistence. Investigation of the initial immune responses to CVB3 may shed light on the mechanisms that contribute to ongoing disease. DCs, as key professional APCs, were investigated in two MHC‐matched hosts: while C57BL/6 mice are resistant to chronic CVB3‐myocarditis, the A.BY/SnJ mouse strain exhibits susceptibility. DC maturation and activation were critically impaired in A.BY/Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…Overall, the 3 major subsets of cDCs in the spleen displayed an activated phenotype within 48 hrs of CVB3 infection, and strongly up-regulated the costimulatory molecule CD86. A recent study examined changes in CD11c + DC phenotype in vivo at 36 hrs post CVB3 infection, but failed to detect a substantial change in MHC class I and II expression at this time point (Rahnefeld et al , 2011). In contrast, our detailed analysis of cDC subsets revealed that CD8α + DCs up-regulate these MHC molecules by 48 hrs p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the 3 major subsets of cDCs in the spleen displayed an activated phenotype within 48 hrs of CVB3 infection, and strongly up-regulated the costimulatory molecule CD86. A recent study examined changes in CD11c + DC phenotype in vivo at 36 hrs post CVB3 infection, but failed to detect a substantial change in MHC class I and II expression at this time point (Rahnefeld et al , 2011). In contrast, our detailed analysis of cDC subsets revealed that CD8α + DCs up-regulate these MHC molecules by 48 hrs p.i.…”
Section: Resultsmentioning
confidence: 99%
“…For immune cell-based assays, splenocytes were obtained as described. 28 For natural killer (NK) cell assays, the NK cell containing cell fraction was enriched by Ficoll density gradient centrifugation (Biocoll, Biochrom) and magnetic cell separation (MACS, Miltenyi).…”
Section: Cell Culture and Plasmidsmentioning
confidence: 99%
“…Interestingly, a subset of DCs expressing TLR3, as well as higher quantities of IL-10 and the proinflammatory cytokines IL-6 and TNF- α , has been shown to be beneficial in the prevention of chronic CVB3 myocarditis [46]. Furthermore, a defect in DCs maturation/activation and DCs MHC class I antigen processing is associated with failure in viral clearance leading to ongoing chronic disease [47]. …”
Section: Immunopathology In Myocarditismentioning
confidence: 99%